ROLE OF RASHTRAKUTA DYNASTY IN THE POLITICS AND CULTURE OF MEDIEVAL SOUTH INDIA - Yadav, Rajnarayan; Singh, Dewanshu Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
There has been disagreement among historians regarding the beginning of the medieval period, where some historians consider it to have started after the 6th century after the fall of the Gupta dynasty while some consider it to have started from the 7th-8th century. After the fall of the Gupta Empire and between the beginning of the Delhi Sultanate, India was divided into many small states. Although many empires tried to reorganize it but could not do so for long. The most important period in this period was the tripartite conflict between the Gurjar-Pratihara, Pala and Rashtrakuta empires and the beginning of the Muslim invasion of India. Some of the dynasties that ruled during that period.